2013
DOI: 10.2478/s13382-013-0092-4
|View full text |Cite
|
Sign up to set email alerts
|

Observance of hand washing procedures performed by the medical personnel before patient contact. Part I

Abstract: Introduction: According to the Centers for Disease Control and Prevention (CDC) as well as the World Health Organi zation (WHO) recommendations, medical staff are obliged to decontaminate the skin of the hands before every single patient contact. Materials and Methods: The study was performed by quasi-observation among the group of 188 medical staff (nurses and physicians) working in three selected hospitals of the Łódź province. The procedure of hand washing and disinfection performed directly before the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
(21 reference statements)
1
21
0
3
Order By: Relevance
“…Further description of the structure of the study groups may be found in the paper by Garus-Pakowska et al [1]. During the observations, 4101 activities were reported as requiring hand hygiene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further description of the structure of the study groups may be found in the paper by Garus-Pakowska et al [1]. During the observations, 4101 activities were reported as requiring hand hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the hand hygiene procedures performed after contact with patients or potentially infectious material in relation to the sum of all observed situations requiring such hygiene procedures showed that medical personnel washed their hands in 26.4% of circumstances which in accordance with the recommendations required such action. Although the percentage of compliance with hand hygiene "AFTER" patient contact is still low (26.4%), the difference relative to hand washing "BEFORE" patient contact (5.2%) [1] is statistically significant (p < 0.001 ) ( Table 1). activities requiring it was 7.5 s for the personnel of "increased risk" departments and 8.3 s for the personnel of the remaining departments (Table 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that hands were washed more frequently after contact with patients than before such contact [9,10], it once again becomes evident that hand hygiene, as an element of protection against infection, is regarded by the medical personnel as being more for their own protection than for the safety of the patients. The observed multiple use of disposable gloves evidently confirms that attitude.…”
Section: Ijomeh 2013;26(3) 427mentioning
confidence: 99%